Complete AV block in a neonatal foal suffering from nutritional myodegeneration. (16th July 2021) - Conze, T. M.; Falkenau, A.; Goehring, L. S.; May, A.
Summary: This case report concerns a 1‐day‐old, full‐term Quarter Horse colt presented due to a progressive inability to rise and nurse. Besides the general weakness, a marked bradycardia was evident, which was caused by a third‐degree atrioventricular (AV) block. Subsequently, the diagnosis of acute nutritional myodegeneration (NMD) was made based on clinical signs, elevated muscle enzymes, ECG findings, as well as low serum selenium and vitamin E values. Despite intensive care and supportive therapy, the foal´s condition deteriorated, and euthanasia was elected. Necropsy confirmed the diagnosis of NMD and revealed diffuse necrosis and inflammatory infiltration of the skeletal and myocardial musculature, as well as the cardiac conduction system which might have resulted in complete AV block.